Experimental Study of Spatiotemporal Variations in Lab-Scale Fire Whirls - Mariko Watanabe; Yuya Oguri (Journal of Combustion)
This study focused on the unsteady behavior of fire whirls. A laboratory-scale fire whirl was generated, and temporal variations in flame height were measured from images taken by a high-speed camera and subjected to frequency analysis. The flame height fluctuations of the fire whirl also showed intermittent behavior, such as the puffing of a pool flame. However, the period and amplitude were irregular compared to the pool flame. In addition, the fire whirl exhibited a greater amplitude spectrum at higher frequencies than the pool flame. To investigate the velocity distribution in the horizontal plane, particle image velocimetry (PIV) was employed. The results demonstrated that the mean velocity increased from the outer radial direction toward the inner radial direction, peaked, and decreased. Conversely, the coefficient of velocity variation decreased from the outer to the inner radial direction, exhibited a minimum, and then increased. Finally, the flame was photographed from horizontal and vertical directions under two conditions with different flow velocities from the fan to generate the fire whirl. Image analysis was employed to investigate the relationship between the center position of the flame and the flame height. The results demonstrated that under conditions where the flow velocity from the fan was low, the fire whirl was intermittent and moved following the circular path drawn by the swirling flow, exhibiting unstable behavior. Furthermore, the flame height was lower when the center of the flame was further from the liquid fuel pool.